Labour unions, public policy and economic growth - Palokangas, Tapio (Cambridge University Press, 2000)
Presents a new theoretical model of union bargaining. It challenges the prevailing view that collective bargaining has a negative impact on welfare and argues that given the existence of market failure, collective bargaining can enhance welfare. For scholars and students in labour economics, public economics, game theory and international economics.